(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2001)
Studies of the chemical composition of Pinus sylvestris L. were performed. The studies embraced all the largest pine populations and the most spread forest types in Latvia. Samples for chemical analyses were taken in 4 stem heights, separately from sapwood and core. The obtained results indicate that the content of cellulose and lignin for trees from different regions and forest types in one stem localization differs moderately. The essential distinctions from the point of view of the chemical composition of pine wood suggests only the extractives content in wood. Common tendencies are observed for the distribution of extractives (EBE) throughout the stem for trees both different regions and forest types. In all stem heights EBE are more in core than in sapwood. To assess the effect of growth conditions on EBE content the results obtained for the same localization in the stem were compared. In all forest types and regions the EBE content in wood is higher as compared with the wood from less ecologically touched regions. In addition the substances extractable with hot water (WE) were determined. It is characteristic that both EBE and WE are less in pine trees grown in drained areas.